Investigation of the Effectiveness of Cognitive Rehabilitation on Working Memory Capacity of Third Grade Students with Special Learning Disabilities (Reading) with a Gender Mediating Role - Raziyeh Norouzbakhsh Haji Kandi (Islamic Azad University, Tabriz Branch, 2021)
This study was carried out by the purpose of determining the effectiveness of cognitive rehabilitation on working memory capacity of third grade students with special learning disabilities (reading) with gender moderation role. The present study is of quasi-experimental type in which pre-test, post-test design with a control group was used. To determine the research sample, the facade test, which is used as a tool to diagnose reading problems and dyslexia of primary school students was performed among the third grade students of Tabriz and the students who got a score higher than the average of the questionnaire were recognized as having a special learning disability (reading) and then among these students, 60 people (four groups of 15 people) were selected by simple random sampling method and randomly divided into two experimental groups (two groups of 15 people, one group was girls and the other group were boys and received cognitive rehabilitation training) and two control. Cognitive rehabilitation training was provided to the experimental group by Smart Sound training software (8-level computer program for cognitive rehabilitation in reading disorder) and working memory was measured using Kretschner (1985) test. Data was analyzed using multivariate factor analysis of covariance. Findings of the research showed that cognitive rehabilitation increases the working memory capacity of students with special learning disabilities (reading) and gender factor has moderating role. Thus, cognitive rehabilitation increases the working memory capacity of students with special learning disabilities (reading) among girls more than boys.